Aarey conservation: A multifaceted opportunity for climate mitigation in an urban setting - Anand Pendharkar; Pranav Bhagwat; Aradhya Sardesai (Amrita Journal of Medicine, 2023)
Citizens of the world are bracing themselves to combat and mitigate cataclysmic climate crisis. Recurrent climate accidents are leaving behind millions of climate refugees, who flock to urban centers in search of safety and security. Overcrowded metropolitan cities are highly vulnerable due to their high human densities and absolute numbers of residents and migrants. A well-connected network of urban green zones (UGZs) provides multiple values that enable sustainable climate mitigation and adaptation. The metropolis of Mumbai, with over 24 million humans (Mumbaikars), is fortunate to also have a network of large UGZs and protected areas (PAs), viz. Sanjay Gandhi National Park, Aarey Milk Colony (AMC), Tungareshwar, Thane, Tansa, and Karnala Wildlife Sanctuaries, along with mangrove forests and public parks. However, most PAs restrict entry and climate mitigation actions. AMC, spread over 12.5 km2 provides a unique “mosaic” landscape, inhabited by indigenous communities (Warli and Mahadev Koli), locals, and migrants. The hills, farms, artificial meadows, and built-up complexes, with a good road network and proximity to Mumbai’s suburbs, provide numerous opportunities to achieve the 17 sustainable development goals set out by members of the United Nations Conference of the Parties. The path to achieve climate and resource stability, in the economic capital of the nation, is a precarious one and needs planning and engagement of all stakeholders. Long-term protection of AMC will provide socioeconomic equity as well as ecological and health security to current and future generations of Mumbaikars.